Analysis of the Diffrence of Completeness of Reporting and Documentation of Laboratory Critical Values Pre and Post-Intervention in Bona Ward Dr. Soetomo Hospital Surabaya - Zubir Zubir; Hartono Kahar; M. Robiul Fuadi; Elly Sulistyani; Tito Yustiawan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Completeness of laboratory critical values reporting and documentation in medical records is important for patient safety, hospital accreditation, and legality. Preliminary study in Dr. Soetomo Hospital’s ward showed the laboratory critical value report and documentation was 0% complete, 4% incomplete, and 96% undocumented. This was a quasi experimental study with one group pretest and posttest design. Technical guidance of laboratory critical values reporting and documentation in medical records and supervision were given to 26 doctors. The results evaluated were doctor knowledge and attitude towards critical value reporting, completeness of documentation in medical records, and turn around time (TAT). Reporting critical values samples number was 72 before and after the intervention. The critical values samples taken by purposive sampling. The data was analyzed using Mann-Whitney test. There were significant differences in the level of knowledge, doctor’s attitudes, and completeness of critical values documentation before and after the intervention. Doctors with good knowledge increased from 3.85% to 92.31%. The attitude to complete critical values documentation improved from 0% to 76%. Completeness of critical values documentation in medical records improved from 100% undocumented to 19.44% undocumented, 11.11% incomplete, and 69.45% complete. There were no significant differences of TAT before and after the intervention, all of TAT were less than 30 minutes and meeting the TAT category. The intervention succeeded in increasing doctor knowledge, attitude, and completeness of the laboratory critical values reporting and documentation in the patient's medical record. Keywords: Laboratory critical value, medical record, turn around time.